2022
DOI: 10.3390/antiox11040789
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary Extracts Improved the Antioxidant Status of Low-Fat Yoghurt Sauces Enriched with Inulin

Abstract: Yoghurt sauces are considered fatty products which are quite susceptible to oxidation and must be stabilised using antioxidants. Novel formulations for yoghurt sauces often involve replacement of fat with dietary fibres and use of natural preservatives. The aim of the present research was to design healthier formulations for yoghurt sauces based on the replacement of sunflower oil (SO) with chicory inulin (IN) and the use of rosemary extracts (RE) as natural antioxidants. Different sauces were developed by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…By increasing the amount of fucoidan added to butter, its antioxidant property increases, so the highest antioxidant property was related to the sample with the highest amount of fucoidan. Another study also showed that with the addition of rosemary and chicory extracts, the amount of antioxidant properties was higher, making it more stable (Martínez‐Tomé et al, 2022 ), which was consistent with the results of this article. However, with the increase in temperature, the stability level decreased compared with the temperature of 110 degrees Celsius ((22.8 ± 0.013–37.8 ± 0.012).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…By increasing the amount of fucoidan added to butter, its antioxidant property increases, so the highest antioxidant property was related to the sample with the highest amount of fucoidan. Another study also showed that with the addition of rosemary and chicory extracts, the amount of antioxidant properties was higher, making it more stable (Martínez‐Tomé et al, 2022 ), which was consistent with the results of this article. However, with the increase in temperature, the stability level decreased compared with the temperature of 110 degrees Celsius ((22.8 ± 0.013–37.8 ± 0.012).…”
Section: Resultssupporting
confidence: 90%
“…Another study also showed that with the addition of rosemary and chicory extracts, the amount of antioxidant properties was higher, making it more stable (Martínez-Tomé et al, 2022), which was consistent with the results of this article. However, with the increase in temperature, the stability level decreased compared with the temperature of 110 degrees Celsius ((22.8 ± 0.013-37.8 ± 0.012).…”
Section: Oxidative Stabilitysupporting
confidence: 89%
“…Therefore, the present study suggested that RE could be considered a promising feed additive for improving specific egg quality characteristics associated with consumer acceptability. We speculated that these beneficial functions may be due to the active ingredients of RE used in this study, which have been reported to play important roles in antioxidant [ 3 ] and anti-inflammatory [ 4 ], as well as regulating intestinal barrier and microbiota and [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rosemary ( Rosmarinus officinalis L.) is a medicinal plant in the Lamiaceae family, which is native to the Mediterranean and widely cultivated throughout the world. Rosemary extract (RE) contains non-volatile active ingredients, which have various pharmacological properties such as antioxidant [ 3 ], anti-inflammatory [ 4 ], antibacterial [ 5 ], anti-apoptotic [ 6 ], and anti-cancer effects [ 7 ]. The bioactive components of RE are mainly diterpenoid phenols, including carnosic acid, carnosol, rosmanol, epirosmanol, rosmaridiphenol [ 8 ], and phenolic acids, including rosmarinic acid, ferulic acid, chlorogenic acid, and caffeic acid [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inulin, a water-soluble storage polysaccharide, is a non-digestible carbohydrate (fructan-type) ( 36 , 37 ). Inulin has been part of the daily diet of humans for centuries and is widely found in ~36,000 plant species, of which chicory root is considered to be the richest source of inulin ( 38 , 39 ).…”
Section: Types Of Prebioticsmentioning
confidence: 99%